Risk of type 2 diabetes and cardiovascular disease in an incident cohort of people with psoriatic arthritis: a population-based cohort study. (6th September 2018) - Charlton, Rachel; Green, Amelia; Shaddick, Gavin; Snowball, Julia; Nightingale, Alison; Tillett, William; Smith, Catherine; McHugh, Neil; ,
Abstract: Objectives: To determine the risk of type 2 diabetes (T2D) and cardiovascular diseases in PsA patients compared with the general population and patients with psoriasis. Methods: Incident PsA patients aged 18–89 years were identified in the UK Clinical Practice Research Datalink between 1998 and 2014 and were matched (1:4 ratio) to a general population cohort and psoriasis cohort. The incidence of T2D, cerebrovascular disease, ischaemic heart disease and peripheral vascular disease (PVD) was calculated for each study cohort. Conditional Poisson regression was used to calculate adjusted relative risks. Results: We identified 6783 incident cases of PsA. The risk of T2D was significantly higher in the PsA cohort than in the general population and the psoriasis cohorts [adjusted relative risk 1.40 (CI95 1.15, 1.70) and adjusted relative risk 1.53 (CI95 1.19, 1.97), respectively]. The incidence of ischaemic heart disease, peripheral vascular disease and the three cardiovascular outcomes combined in the PsA cohort was significantly higher than in the general population. No significant differences in risk were observed between the PsA and psoriasis cohorts for any cardiovascular outcome. Conclusion: The development of T2D in an incident population of PsA is significantly higher than in psoriasis alone or in a general population, whereas the increased risk of cardiovascular disease in PsA and psoriasis is similar.